2014
DOI: 10.1007/s12032-014-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-specific protease 14 (USP14) regulates cellular proliferation and apoptosis in epithelial ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) is the most lethal gynecologic malignancy. Thus, there is an emergent need to invest a novel therapeutic for EOC. In this study, we defined ubiquitin-specific protease 14 (USP14) as a therapeutic target for EOC. Western blot was used to evaluate the expression of USP14 in nine fresh EOC tissues and three fresh normal ovarian tissues. The protein level of USP14 was higher in the cancer samples compared with that in the normal ovary tissues. Immunohistochemistry analysis was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 24 publications
5
51
0
Order By: Relevance
“…USP14 is strongly expressed in MM cells (Supplementary Fig. 4a) and has also been reported to be overexpressed in other malignancies such as ovarian and hepatocellular carcinoma3435. We found that knock-down of either USP14 or UCHL5 in multiple myeloma cells resulted in loss of cell viability, consistent with our previous results36 and those of other investigators using hepatocellular carcinoma and ovarian cancer cells3435.…”
Section: Discussionsupporting
confidence: 91%
“…USP14 is strongly expressed in MM cells (Supplementary Fig. 4a) and has also been reported to be overexpressed in other malignancies such as ovarian and hepatocellular carcinoma3435. We found that knock-down of either USP14 or UCHL5 in multiple myeloma cells resulted in loss of cell viability, consistent with our previous results36 and those of other investigators using hepatocellular carcinoma and ovarian cancer cells3435.…”
Section: Discussionsupporting
confidence: 91%
“…Inhibition of ІRE1 signaling enzyme function in U87 glioma cells increased effect of glutamine deprivation on the expression of USP1 gene and introduced sensitivity of USP4 and USP14 genes to this condition. A decreased level of USP1, USP4, and USP14 mRNA expression upon glutamine deprivation agrees well with functional role of these enzymes and suppression of glioma cell proliferation, because there is data that USP1 targeting impedes GBM growth and that USP4 and USP14 regulate cellular proliferation and apoptosis [16,18,23].…”
Section: Resultssupporting
confidence: 65%
“…In agreement, microRNA-191 mediated lower protein level of USP10 has been demonstrated to promote pancreatic cancer progression [21]. It was shown that USP14 is a tumor promoting peptidase, its phosphorylation and activation by Akt not only regulates the ubiquitin-proteasome system, but also promotes tumor progression through regulation of cellular proliferation and apoptosis of cancer cells [23]. Inhibition of USP14 could be used as potential anti-cancer therapeutic strategy.…”
mentioning
confidence: 84%
“…These results suggest that activated Akt in Pten-negative cancer cells might be able to stabilize a significant portion of the proteome by inhibiting both UPS and autophagy through regulating USP14 to promote tumorigenesis. Consistent with this possibility, increased expression of USP14 has been found in a variety of cancers, including multiple myeloma (Tian et al 2014), colorectal cancer (Shinji et al 2006), lung cancer (Wu et al 2013), epithelial ovarian cancer (Wang et al 2015), and endometrial cancer (Vogel et al 2016). Future studies will be needed to elucidate the functional role of elevated USP14 expression in tumorigenesis.…”
Section: Discussionmentioning
confidence: 78%